(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Employing a GIS-RS integrated approach, the research assesses the concentrations of air quality parameters including nitrogen dioxide (NO2), sulfur dioxide (SO2), carbon monoxide (CO), and Aerosol Optical Depth (AOD) across different land cover features in the south-central coastal area of Bangladesh over a six-year period. It also investigates the seasonal variation in air quality parameters. The study reveals that high level of CO and NO2 concentration was seen across built-up and agricultural areas. Across waterbodies high level of SO2 and AOD concentration was found. Further analysis reveals a consistent increase in NO2 concentration, especially in winter seasons with the lowest values at 0.000021 mol/m2 in 2019 and the highest at 0.000064 mol/m2 in 2023. Moreover, SO2 exhibits fluctuating patterns with highest level of concentration being observed in the winter seasons (i.e., 0.0001384 to 0.0005533) mol/m2. Similar pattern was observed in seasonal CO concentration levels, while AOD concentrations depicts a different picture with high level of concentration observed across monsoon seasons. The study addresses the knowledge gap of identifying high pollution concentration zones across land cover features in the study area. It also provides valuable insights into the seasonal variations of air quality parameters in the study area. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 69-89